Indoor cat : how to enrich their lives and expand their world - Moss, Laura J.; Bahr, Lynn (Running Press, 2022)
Can an indoor cat live a happy, stimulating, and active life? Veterinarian Lynn Bahr and journalist Laura J. Moss answer this question with a resounding yes, and offer real-life guidance for opening up your cat's world, even if they stay within the confines of your home. There are many myths our culture perpetuates about domestic cats: they live longer indoors, sleep all day, are easy and low-maintenance pets, and can't be trained. Even the most well-meaning kitty caregiver will be surprised to learn that these long-held beliefs aren't necessarily based on facts, but instead reflect the many ways we have adapted our feline friends to our indoor, domesticated lifestyles. Indoor Cat, by Laura J. Moss, journalist and founder of Adventure Cats, and Lynn Bahr, a feline-only veterinarian, explores how to help cat owners understand a cat's perspective of their indoor homes, with practical ways to enhance cats' lives to the fullest and combat countless health and behavioral problems that result from indoor living, as well as raising the question: should every cat live exclusively indoors? Together with scientific studies, expert opinions with vets and behaviorists (including Jackson Galaxy and America's Veterinarian Dr. Marty Becker), and firsthand accounts and interviews, this informative and engaging guide strives to reach compassionate cat owners looking for new ways to care for and connect with their feline companions. Included throughout are 100 full-color photos.